Comparison of the performance of the pyrolysis processes of PET, LDPE and PS, in a prototype batch process reactor - Torres, Jorge; Vinces, Milton; Castro, Pedro; Arias, Jaime (EASI: Engineering and Applied Sciences in Industry, 2025)
In this study, the critical factors of the pyrolysis process of plastics to obtain liquid hydrocarbons derived from petroleum were determined. The evaluation of these factors consisted of tests at specific temperatures of 350, 395 and 400 °C using different types of plastics, such as polyethylene terephthalate (PET), polystyrene (PS) and low-density polyethylene (LDPE). The tests were carried out in a batch reactor with an average reaction time of 10 minutes. It was found that PS, processed at 395 °C for 8 minutes, produced the highest number of liquid hydrocarbons, with an average yield of 91% by weight compared to the liquid products. In contrast, PET generated less than 30% product, while LDPE achieved a yield of 84%. The determining factors were the average temperature, the thermal insulation of the reactor and the selection of the type of plastic. Other factors, such as pressure and reaction rate, also proved to have a relevant impact on the process results.
Keywords: Pyrolysis of plastics; liquid hydrocarbons; reactor; plastics; critical factors